Regarding the identification of main features of improvement and harmonization of market agents relations in welfare economics - Варцаба, В. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
In the article, the existence of a direct connection between the fact of reaching a paretooptimal market state by any system as a consequence of achieving and sustaining harmonized relationships between all of its sharers, is proved on the basis of the analysis of theoretical principles, definitions, categories, patterns and characteristics of welfare economics and the conception of social prosperity. The causes of the state of the lacking optimality of the market because of the disharmony of the relationships in the system have been demonstrated. A new, inherent to pro-industrial, informationalintellectual economy, resource factor – intellectual resource, ensuring an effective use of which will guarantee an optimization of distribution of all the other resources of the system with the achievement of a higher level of social well-being, has been identified. It has been determined that further research has to be aimed at identifying the conditions that ensure an effective interaction of individuals or their groups on the basis of their ability and disposition to the harmonization of their and else’s interests, and to the establishment of economic harmony of interests and benefits.